QUESTIONING THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY - Arzieva Hurliman (International Journal of Literature and Language Studies, 2026)
This study examines the relationship between grammar mastery and writing ability among secondary school students. While grammar is often considered a foundation for writing competence, this paper questions the extent to which grammatical proficiency truly determines writing performance. Drawing on classroom-based observations and the analysis of the 'Past Tenses Mystery and Recurrent Composition' task, this study suggests that communication skills and contextual awareness can sometimes compensate for limited grammatical accuracy. Findings imply that while grammar facilitates clarity, writing ability ultimately depends on broader cognitive and creative processes.